2010
DOI: 10.3917/th.724.0383
|View full text |Cite
|
Sign up to set email alerts
|

L'acceptabilité sociale : la prise en compte des déterminants sociaux dans l'analyse de l'acceptabilité des systèmes technologiques

Abstract: RÉSUMÉ L’étude de l’acceptabilité renvoie à de nombreux modèles (Modèle d’acceptation des technologies : Davis, Bagozzi, & Warshaw, 1989 ; P3, Pouvoir, performance, perception : Dillon & Morris, 1999 ; ou encore Unified Theory of Acceptance and Use of Technology : Venkatesh, Morris, Davis, & Davis, 2003) pour prédire le comportement de l’utilisateur. Dans ces modèles le poids des variables sociales pour prédire l’intention d’usage ou le comportement de l’utilisateur est variable (de .02 à .51). Cet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 30 publications
1
34
0
5
Order By: Relevance
“…Indeed, it had been shown that practicing regularly a new technology might lead to automation complacency bias (Terrade et al, 2009), defined as a psychological state characterized by a low index of suspicion (Wiener, 1981). In other words, when someone is assisted by an automated device and has to switch from performing a task himself or herself to monitoring the operation, he or she can face difficulties to react efficiently when the device fails (Parasuraman et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it had been shown that practicing regularly a new technology might lead to automation complacency bias (Terrade et al, 2009), defined as a psychological state characterized by a low index of suspicion (Wiener, 1981). In other words, when someone is assisted by an automated device and has to switch from performing a task himself or herself to monitoring the operation, he or she can face difficulties to react efficiently when the device fails (Parasuraman et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Technology acceptability deals specifically with perceived usefulness and perceived ease of use (Davis, 1989). Technology a priori acceptability should be addressed considering the evaluation of the technology itself and the methodology used to evaluate it (Bagozzi, 1981), as well as its potential uses, which is possible (Laurencin, Hoffman, Forest & Ruffieux, 2004;Terrade, Pasquier, Reerinck-Boulanger, Guingouain, & Somat, 2009). …”
Section: A Priori Acceptability Attitudes and Intention To Use Autommentioning
confidence: 99%
“…The social acceptance of technology approach attempts to understand users' behavior when confronted with using technologies (Bobillier-Chaumon & Dubois, 2010;Terrade, Pasquier, Boulanger, Guingouain, & Somat, 2009). Emphasis is placed on the importance of users' perceptions, social representations, behaviors, and attitudes by integrating social and normative dimensions, which are known to affect the motivations for choosing to use a specific system.…”
Section: Social Acceptance Of Technologymentioning
confidence: 99%
“…Each scenario was followed by two items measuring one's attitude towards theft. Acceptability has been suggested as one of the main dimensions of attitudes and has been used as a tool for assessing attitudes in a number of studies (e.g., De Groot & Steg, 2009;Posthuma & Dworkin, 2000;Terrade, Pasquier, Reerinck-Boulanger, Guingouain, & Somat, 2009). Therefore, we measured attitudes towards theft was by assessing the acceptability dimension of attitudes towards theft, measured on a 7-point likert-type scale ranging from "very unacceptable" to "very acceptable".…”
Section: Procedures and Materialsmentioning
confidence: 99%